Rethinking the victim : gendered violence in Australian women's literature - Brewster, Anne, and Kossew, Sue; Kossew, Sue (London: Routledge, 2019)
"Rethinking the Victim: Gendered Violence in Australian Literature is the first comprehensive investigation of the multiple and interrelated forms of violence which play out across intimate, familial, colonial and militarised zones in Australian women's literature. Arguing that gendered violence is inflected with sexuality, class, race, ethnicity and many other factors, the book rethinks victimhood and agency from a feminist perspective and resists the spectacularization of violence against women that is often graphically depicted in cinema, news media and pornography"--
Intimate violations: Gothic and Romance -- Violence against women and girls: Indigenous women's activist poetry -- Broken families, vulnerable children -- War and political violence.
Includes bibliographical references and index.
Keywords: Australian literature; Australian literature; Violence in literature; Sex role in literature